2022
DOI: 10.1007/s10530-022-02824-4
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of invasive alien species with the potential to threaten agriculture and biodiversity in Kenya through horizon scanning

Abstract: Invasive alien species (IAS) rank among the most significant drivers of species extinction and ecosystem degradation resulting in significant impacts on socio-economic development. The recent exponential spread of IAS in most of Africa is attributed to poor border biosecurity due to porous borders that have failed to prevent initial introductions. In addition, countries lack adequate information about potential invasions and have limited capacity to reduce the risk of invasions. Horizon scanning is an approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Workshops have involved training on the tool itself and capacity building in low‐ and middle‐income countries where limited resources mean that routine horizon scanning, pest risk assessment and prioritization activities present a particular challenge. Workshops were held in Kenya and Ghana in 2018–2019 to establish a list of plant pests that were absent from each of the countries but that posed a potential risk to agriculture and/or the environment should they arrive (Kenis et al., 2022; Mulema et al., 2022). Both workshops involved subject matter experts from research and academia, including risk assessors from the NPPO.…”
Section: How To Evaluate Emerging Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Workshops have involved training on the tool itself and capacity building in low‐ and middle‐income countries where limited resources mean that routine horizon scanning, pest risk assessment and prioritization activities present a particular challenge. Workshops were held in Kenya and Ghana in 2018–2019 to establish a list of plant pests that were absent from each of the countries but that posed a potential risk to agriculture and/or the environment should they arrive (Kenis et al., 2022; Mulema et al., 2022). Both workshops involved subject matter experts from research and academia, including risk assessors from the NPPO.…”
Section: How To Evaluate Emerging Risksmentioning
confidence: 99%
“…The pilot programme ran for 8 months in 2022 with the NPPOs in Kenya, Ghana, Burkina Faso and Zambia. A total of 120 pests were monitored, including those identified through the horizon scanning activities carried out in Ghana and Kenya (Kenis et al., 2022; Mulema et al., 2022). Results were disseminated monthly to each NPPO in a newsletter format.…”
Section: Reportingmentioning
confidence: 99%
“…The risk scoring system used was based on that described by Roy et al (2019). This scoring system (guidelines) had been modi ed in previous studies by Mulema et al (2022) and Kenis et al (2022). Roy et al (2019) assessed the likelihood of arrival, establishment, spread, and magnitude of potential negative impact on biodiversity and ecosystem services whereas in this assessment, the likelihood of entry (arrival), establishment, and potential magnitude of socioeconomic impact and potential magnitude of impact on biodiversity were assessed.…”
Section: Description Of the Scoring Systemmentioning
confidence: 99%
“…However, some IAS arrive into new environments unaided such as the iers or facilitated by natural means such as storms, hurricanes and wind currents (Westphal et al 2008;Desneux et al 2011;Nagoshi et al 2018). In SSA, lack of awareness, facilitated by lack of or limited enforcement of laws, porous borders, and weak border biosecurity have played a signi cant role in the introduction and spread of IAS (Mulema et al 2022) as observed in previous years (Desneux et al 2011;Mahuku et al 2015; Day et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation